Pulmonary exacerbation in adults with bronchiectasis: a consensus definition for clinical research. Issue 6 (8th June 2017) - Hill, Adam T.; Haworth, Charles S.; Aliberti, Stefano; Barker, Alan; Blasi, Francesco; Boersma, Wim; Chalmers, James D.; De Soyza, Anthony; Dimakou, Katerina; Elborn, J. Stuart; Feldman, Charles; Flume, Patrick; et al.
There is a need for a clear definition of exacerbations used in clinical trials in patients with bronchiectasis. An expert conference was convened to develop a consensus definition of an exacerbation for use in clinical research. A systematic review of exacerbation definitions used in clinical trials from January 2000 until December 2015 and involving adults with bronchiectasis was conducted. A Delphi process followed by a round-table meeting involving bronchiectasis experts was organised to reach a consensus definition. These experts came from Europe (representing the European Multicentre Bronchiectasis Research Collaboration), North America (representing the US Bronchiectasis Research Registry/COPD Foundation), Australasia and South Africa. The definition was unanimously approved by the working group as: a person with bronchiectasis with a deterioration in three or more of the following key symptoms for at least 48 h: cough; sputum volume and/or consistency; sputum purulence; breathlessness and/or exercise tolerance; fatigue and/or malaise; haemoptysis AND a clinician determines that a change in bronchiectasis treatment is required. The working group proposes the use of this consensus-based definition for bronchiectasis exacerbation in future clinical research involving adults with bronchiectasis. An expert conference has developed a consensus definition of a bronchiectasis exacerbation for clinical research http://ow.ly/oKPY309yTaX